Impact of sustainable land‐use management practices on soil carbon storage and soil quality in Goa State, India. (1st November 2021) - Paramesh, Venkatesh; Singh, Surendra Kumar; Mohekar, Deepak S.; Arunachalam, Vadivel; Misra, Shiva Dhar; Jat, Shankar Lal; Kumar, Parveen; Nath, Arun Jyoti; Kumar, Nirmal; Mahajan, Gopal Ramdas; Bhagat, Tejasvi
Abstract: Evaluating sustainable land management (SLM) practices have regional to worldwide implications. It is imperative to develop SLM under particular soil type, climate, and cropping sequence following area‐specific best management practices to harness maximum profitability. The alternative land‐use system (ALUS—natural forest, pasture, cashew, areca nut, coconut) on hills and agricultural land‐use system (AGLUS—rice–rice, rice–pulse) in the coastal plains of Goa State in west coast India were evaluated in this study. This study assessed the impact of sustainable land‐use management practices on different fractions of soil organic carbon (SOC), its stock, and soil quality index (SQI) under the ALUS and AGLUS. The total SOC stocks under different land‐use systems varied from 14.4 Mg C ha −1 in rice–rice rotations to 133.7 Mg C ha −1 in cashew. The lability index, available nutrients, and biochemical properties were higher in ALUS. The variation in the levels of SOC and soil quality was due to land use and management practices. The results indicated land use with areca nut (SQI = 0.8) on the hills and rice–pulses (SQI = 0.25) rotations on the coast had maintained soil quality of high order. We recommend promoting sustainable agriculture with ALUS on the hills and AGLUS on the coastal plains of Goa State to enhance SOC storage, improve soil quality, and increase farmers' income.